Coupling Electrocatalytic CO2 Reduction with Thermocatalysis Enables the Formation of a Lactone Monomer. Issue 10 (25th March 2021) - Ponsard, Louise; Nicolas, Emmanuel; Tran, Ngoc Huan; Lamaison, Sarah; Wakerley, David; Cantat, Thibault; Fontecave, Marc
Abstract: Carbonylation reactions that generate high‐value chemical feedstocks are integral to the formation of many industrially significant compounds. However, these processes require the use of CO, which is invariably derived from fossil‐fuel‐reforming reactions. CO may also be generated through the electroreduction of CO2, but the coupling of these two processes is yet to be considered. Merging electrocatalytic reduction of CO2 to CO with thermocatalytic use of CO would expand the range of the chemicals produced from CO2 . This work describes the development of a system coupling a high‐pressure CO2 electrolytic cell containing a bimetallic ZnAg catalyst at the cathode for production of CO with a reactor with a Faradaic efficiency of >90 % where high pressure CO is used for carbonylating propylene oxide into β‐butyrolactone by thermal catalysis, the latter step having a reaction yield above 80 %. Although the production of monomers and polymers from CO2 is currently limited to organic carbonates, this strategy opens up the access to lactones from CO2, for the formation of polyesters. Abstract : Best of both worlds : The synthesis of carbonyl‐containing compounds from CO2 by coupling CO2 electroreduction and thermocatalytic conversion of CO constitutes an efficient approach for the recycling of carbon atoms in high‐value chemicals. The formation of β‐lactone, a precursor of polyester, is achieved at high pressure from CO2 through the formation of CO as a reactive intermediate.